Influence of crop combinations and soil factors on diversity and association of arbuscular mycorrhizal fungi in arecanut based cropping systems - Ambili, K.; Thomas, George V.; Alka Gupta, Murali Gopal (Journal of Plantation Crops, 2017)
Arbuscular mycorrhizal (AM) species diversity and extent of association were investigated in arecanut based cropping systems differing in crop combinations. The study was carried out in farmers’ fields under acidic soil conditions at three locations representing low land (Maneikkara), midland (Cheruvanjeri) and high land (Nedumpoyil) regions of Kannur district in Kerala. The cropping systems in Maneikkara, Cheruvanjeri and Nedumpoyil had arecanut-banana, arecanut-banana-black pepper and arecanut-bananablack pepper-cardamom as component crops. AM spore load and root colonization differed significantly in arecanut in the three cropping systems. Highest spore load was recorded in Maneikkara followed by that in Nedumpoyil and Cheruvanjeri regions. Crops which formed components of the cropping system differed in root colonization levels, with banana recording the highest level, followed by arecanut, black pepper and cardamom. Colonization pattern was Paris type in all crops, but varied with respect to predominance of arbuscules in arecanut and vesicles in banana. Arecanut-black pepper-banana system at Cheruvanjeri in midland was superior with respect to species diversity and species richness as evidenced by Shannon–Weiner index (Hs), Simpson’s index of diversity (Ds) and species richness index. Arecanut-banana cropping system in Maneikkara in low land had low level of species diversity and species richness, indicating the combined influence of crop combinations and soil factors such as N and P on AM diversity and distribution. Rhizophagus fasciculatus, Funneliformis geosporum, F. mosseae, Glomus macrocarpum, G. aggregatum, G. multicaule, G. glomerulatum and Acaulospora bireticulata were the AMF species identified from the arecanut cropping systems. F. geosporum was the most abundant (29-50%) species in the cropping system. The relative occurrence and abundance of AM species varied significantly with respect to the crops and locations.